Number of Natural Teeth and Oral Impacts: A Study on Sri Lankan Adults - Roshnal Perera; Lilani Ekanayake (International Journal of Dentistry)
The aim of the study was to determine the association between the number of natural teeth and oral impacts in Sri Lankan adults. The sample consisted of 476, 40–59 and 452, ≥60 year olds. Oral impacts were assessed using a validated Sinhalese translation of the Oral Health Impact Profile-14 scale. A receiver-operating characteristic (ROC) curve was plotted to determine the number of natural teeth that would best discriminate those with oral impacts from those without. Oral impacts were reported by 26% of the 40–59 year olds and 34% of the older individuals. In both groups there was a significant negative correlation between the number of teeth present and oral impacts. The ROC curve for the 40–59 year olds gave an area under the curve (AUC) of 0.758 (95% CI = 0.702–0.814; 𝑃<0.001) with an optimal cut-off of 24/25 teeth while for the ≥60 year olds, the AUC of the ROC curve was 0.737 (95% CI = 0.684–0.790; 𝑃<0.001) with an optimal cut-off of 18/19 teeth. Based on the ROC curves the optimal cutoffs of the number of natural teeth that best discriminated between those with and without oral impacts for 40–59 and ≥60 year olds were 24-25 and 18-19, respectively.